MEDIA PEMBELAJARAN PLC ENGINEERING SUPPORT BERBASIS CONSOLE MENGGUNAKAN FLASH (Information Technology and Telematics, 2015)
Abstrak-Development of Plc systems (Programmable Logic Control) at the moment there are several things that must be considered, namely how to study and analyze from a manual system to an automated system. The use of the system Plc are now widely used in various industrial equipment or other services Plc systems play an important role in the activities of manufacturing or industrial activities of goods or services. Because the control system is a very complex plc certainly to perform repairs or maintenance Plc systems require concentration to solve various problems that occur. In the industrialized world novice technicians require incentives for learning basic training - the basic logic to analyze or make improvements in the control systemPlc. The user of the console is one of the means of control are versatile and widely used for editing ladder programs are very helpful in the control system that is simple Simulation plc learning this function is to provide information in the form of animation, the aim is to provide a real picture in virtual form, how the concept of working from .Aplikasi Plc used is Adobe Flash CS3, it is appropriate applications are used to manufacture the simulation engine that can be controlled by plc Keywords: Systems Plc (Programmable Logic Control, Console, Flash diagnosis damage